(untitled) (Scientific Journal of Actuarial Finance and Accounting, 2024)
In this article, factors such as the price policy of the enterprise, the tasks and mechanism of development, the goals and tasks of the enterprise's development, the organizational structure and management methods, the traditions established in the enterprise, the state and development of the business environment as external factors are considered.